Soft Tissue Coverage of the Mangled Upper Extremity - Ng, Zhi Yang; Salgado, Christopher J.; Moran, Steven L.; Chim, Harvey (Seminars in Plastic Surgery, 2015)
Mangled upper extremity injuries usually involve high-impact trauma with crushing and tearing of the limb and its associated soft tissue structures. Such trauma is particularly mutilating because of the nature of the injury and the involvement of structures vital for proper function. Although advancements in flap technique and improvements in bone fixation methods have enabled good functional and clinical outcomes in limb salvage reconstruction, this remains a challenging area. Attempts at limb preservation should be fully exhausted before consideration is given for amputation, which results in significantly decreased function. Here the authors focus on the various modalities of soft tissue coverage available including allogenic substitutes, the adjunctive use of negative pressure wound therapy, and the design and utilization of flaps to address various defect configurations for the goals of wound healing, aesthetics, and functional restoration in the mangled upper extremity.
Keywords: upper extremity; hand; injury; soft tissue flap